Analisisis Statistik Pertandingan Tim Juara Basket Putra Universitas Semarang pada Pertandingan Soegijapranata Basketball League 2026 - Aulia Adinda Safitri; Priyanto (MAN Insan Cendekia Jambi, 2026)
Currently, the context of competitions, especially basketball championships, is in need of data used to evaluate player performance by using statistics from ongoing matches. The purpose of this study is to analyze the match data of the Semarang University Men’s Basketball Team in the 2026 Soegijapranata Basketball League Championship. The method applied in this study is a descriptive quantitative method using a statistical document analysis approach with data sourced from FIBA Livestats. The data obtained was from five matches that took place from February 4 - 14, 2026, so the analysis results showed that factors in the form of internal factors, namely the team’s drive to defend and control field goals through rebound efficiency, which is categorized as high. In addition, the players also showed discipline in terms of field goals efficiency, which was 83,3% categorized as medium overall. However, efficiency in turnover was one of the main weaknesses, with an efficiency of 66,7% categorized as medium. Indirectly, although the players have a solid defense and ball management, they still need to strengthen their accuracy in three-point shots and balance the point contributions among players to improve their performance.